CHF6297: a novel potent and selective p38 MAPK inhibitor with robust anti-inflammatory activity and suitable for inhaled pulmonary administration as dry powder - Martucci, Cataldo; Allen, Andrew Dennis; Moretto, Nadia; Bagnacani, Valentina; Fioni, Alessandro; Patacchini, Riccardo; Civelli, Maurizio; Villetti, Gino; Facchinetti, Fabrizio (Frontiers in Pharmacology, 2024)
Inhibition of p38 mitogen-activated protein kinases (MAPK) is a potential therapeutic approach for the treatment of acute and chronic pulmonary inflammatory conditions. We report here the in vitro and in vivo characterization of the anti-inflammatory effects of CHF6297, a novel potent and selective p38α inhibitor designed for inhalation delivery as dry powder formulation. CHF6297 proved to inhibit p38α enzymatic activity with sub-nanomolar potency (IC50=0.14±0.06 nM) with >1000-fold selectivity against p38γ and p38δ. In human PBMCs stimulated with LPS, as well as in human bronchial epithelial cells (BEAS2B) stimulated with TNF-α or cigarette smoke extract (CSE), CHF6297 inhibited IL-8 release with low nanomolar potency. CHF6297 administered to rats by a nose only inhalation device as micronized dry powder formulation blended with lactose, dosedependently inhibited LPS-induced neutrophil influx in the bronchoalveolar lavage fluid (BALF).CHF6297 administered intratracheally to rats, dose-dependently counteracted IL-1β (0.3 mg/kg)induced neutrophil influx (ED50=0.22mg/kg) and increase in IL-6 levels (ED50=0.82 mg/kg) in BALF. In mice exposed to tobacco smoke (TS), CHF6297, administered intranasally (i.n.) for 4 days at 0.03 or 0.3 mg/kg, dose-dependently inhibited the corticosteroid-resistant TS-induced neutrophil influx in BALF. In a murine house dust mite (HDM) model of asthma exacerbated by influenza virus A (H3N3), CHF6297 (0.1 mg/kg, i.n.) significantly decreased airway neutrophilia compared to vehicle treated IAV/HDM challenged mice. When CHF6297, at a dose ineffective per se (0.03 mg/kg), was added to budesonide, augmented the anti-inflammatory effects of the steroid.Overall, CHF6297 effectively counteracted lung inflammation in experimental models where corticosteroids exhibit limited anti-inflammatory activity, suggesting a potential for the treatment of acute exacerbations associated with COPD and asthma, acute lung injury (ALI) and viral-induced hyperinflammation.